FBP1 Is an Interacting Partner of Menin. (14th July 2014) - Zaman, Shadia; Sukhodolets, Karen; Wang, Patricia; Qin, Jun; Levens, David; Agarwal, Sunita K.; Marx, Stephen J.
Abstract : Multiple endocrine neoplasia type 1 (MEN1) is a syndrome characterized by tumors in multiple endocrine tissues such as the parathyroid glands, the pituitary gland, and the enteropancreatic neuroendocrine tissues. MEN1 is usually caused by mutations in the MEN1 gene that codes for the protein menin. Menin interacts with proteins that regulate transcription, DNA repair and processing, and maintenance of cytoskeletal structure. We describe the identification of FBP1 as an interacting partner of menin in a large-scale pull-down assay that also immunoprecipitated RBBP5, ASH2, and LEDGF, which are members of complex proteins associated with SET1 (COMPASS), a protein complex that methylates histone H3. This interaction was confirmed by coimmunoprecipitation and Flag-pull-down assays. Furthermore, menin localized to the FUSE site on the MYC promoter, a site that is transactivated by FBP1. This investigation therefore places menin in a pathway that regulates MYC gene expression and has important implications for the biological function of menin.